Lesson study in Dutch initial teacher education explored: its potential and pitfalls. Issue 4 (24th July 2020) - Schipper, Tijmen M.; Goei, Sui Lin; Van Joolingen, Wouter R.; Willemse, T. Martijn; Van Geffen, Evelien C.
Abstract : Purpose: This paper explores the potential and pitfalls of Lesson Study (LS) in Dutch initial teacher education (ITE). This context is examined through data drawn from student-teachers and teacher educators participating in LS. Design/methodology/approach: Three case studies of three teacher education institutes in the Netherlands are presented, focusing on student-teachers' learning in two cases and teacher educators' learning in the third case. Findings: The case studies show that LS in the context of Dutch ITE has high potential. All cases yield clear benefits for working collaboratively as a result of participating in a LS. Student-teachers appreciate the explicit focus in LS on how students learn and teacher educators stress how LS may strengthen their role as "teachers of teachers." Time, planning arrangements, commitment and a LS facilitator are highlighted as essential conditions for LS application in ITE. Research limitations/implications: The three cases address a specific ITE context focusing on different target groups (student-teachers and teacher educators in applied and/or research universities). Consequently, results are explorative regarding Dutch ITE. Practical implications: The potential of LS in Dutch ITE is recognized and stressed; this study may act as a catalyst for further and wider application of LS in this context, taking into account possible pitfalls and conditions. Originality/value: This is one of the first studies exploring the potential of LS in Dutch ITE using both student-teachers' and teacher educators' perspectives.